Using quantitative methods for a student study activity analysis in a virtual learning environment concerning different students' backgrounds - Lauc, Tomislava; Bago, Petra; Kišiček, Sanja (2011)
This research deals with an application of quantitative methods to analyze student study activities in Moodle, an open source virtual learning environment (VLE). The aim is to determine how students' backgrounds influence their knowledge achievements. The research was performed using student activities’ log analysis in an Information Sciences course at the Faculty of Humanities and Social Sciences, University of Zagreb. The course is conducted as a fully online course on a graduate level. The data analysis is based on log analysis considering number of (re)accessed resources and number of (re)accessed assignments. Also, two indicators, time of assignment submission and number of (re)submitted assignments are used to calculate final results for every course participant. In order to gather information about students’ knowledge backgrounds, they were asked to answer survey questions. Research data reveals that, with respect to different knowledge backgrounds, there is no significant difference regarding students’ achievements.
Projekt MZOS
Projekt MZOS
ENG